(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The economical units in the world face great and rapid challenges in all aspects, a matter that requires facing these challenges throughout continuous improving and developing in their performance to keep their competitive position "place". The Benchmarking Technique is one of the modern managerial tools that are proved to be successful in application throughout making continuous comparisons between products or services and the best – performance levels the compete with it . This is achieved to develop its performance and give it the competitive criterion with which it faces its competitors. The present research aims at applying the Benchmarking Technique in the Institutions of Higher Education in Iraq to show the role it plays in developing the curricula of the Accounting Departments in Iraqi Universities throughout comparing them with those of the Department of Accounting in AL- Malik Su’od University.